The discovery of early childhood : the development of services for the care and education of very young children, mid eighteenth century Europe to mid twentieth century New Zealand - May, Helen, 1947- (Auckland University Press/Bridget Williams Books, 1997)
The challenge of liberalism and enlightenment: childhood, learning, and motherhood. The ills of childhood: destitution, foundlings, and baby-farming. Froebel kindergartens: educational innovation, philanthropy, and feminism. Creche and nursery care...